A TYPOLOGY OF MALE CONSUMERS ON THE MEN’S ELEGANT FASHION MARKET: CASE STUDY OF POLAND - Maciejewski, Grzegorz; Lesznik, Dawid (Acta scientiarum Polonorum. Ekonomia. Oeconomia, 2022)
The authors of the presented article conducted primary research among contemporary gallants, aiming to identify consumer types within the niche of elegant men’s clothing, including possible dandies. In the conducted study, online surveys were posted on internet forums and thematic groups focused on Polish male smart dressers. As many as 30% of respondents considered themselves as dandies, and three types of customers were distinguished: exacting sartorialists, low-budget gallants and phonies. The difference between the first two is mainly due to disparities in purchasing budgets. Phonies, on the other hand, appear to be superficial in purchase decisions, perhaps gaining interest in an elegant style only as a temporary whim. The results will prove useful for brands in the men’s elegance segment, broadly highlighting the in-depth characteristics of different customer groups. Moreover, contrary to the subject literature, the research shows that dandyism is still a lively trend.